2003
DOI: 10.1093/ps/82.10.1500
|View full text |Cite
|
Sign up to set email alerts
|

Growth, livability, and feed conversion of 1957 versus 2001 broilers when fed representative 1957 and 2001 broiler diets

Abstract: Body weight, feed consumption, and mortality were measured in the 1957 Athens-Canadian Randombred Control (ACRBC) strain and in the 2001 Ross 308 strain of broilers when fed representative 1957 and 2001 diets. The dietary regimens were chosen to be representative of those used in the industry in 1957 vs. 2001. The 1957 diets were fed as mash, the 2001 starter was as crumbles, and the grower and finisher diets were pellets. Feed consumption and BW were recorded at 21, 42, 56, 70, and 84 d of age to cover the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
342
0
20

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(383 citation statements)
references
References 13 publications
11
342
0
20
Order By: Relevance
“…This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype. Franco et al (2012Franco et al ( , 2013) also found great difference in meat quality traits between Mos and Sasso T-44 roosters.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 91%
“…This result confirms the finding of Youssao et al (2010) who showed that indigenous chicken populations of Benin are characterized by a great genetic diversity than that reported for commercial lines chicken (Granevitze et al, 2007;Muchadeyi et al, 2007;Berthouly et al, 2008). In accordance with Havenstein et al (2003aHavenstein et al ( , 2003b, technological and nutritional meat quality depend on genotype. Franco et al (2012Franco et al ( , 2013) also found great difference in meat quality traits between Mos and Sasso T-44 roosters.…”
Section: Discussion Correlations Between Technological and Nutritionasupporting
confidence: 91%
“…When placed on the 1950s diet, modern broilers were much smaller but slightly leaner than those placed on the modern diet, nevertheless fatter than the old-type birds. When placed on the more balanced modern diet, which had a higher energy and protein content (Havenstein et al 1994a(Havenstein et al , 2003b, the old-type birds became fatter at every age than they did when fed on the 1950s diet. It is likely that the less-balanced 1950s diet did not contain enough nutrients required by the modern breed each day to reach its full genetic potential and so this led to a reduced growth rate.…”
Section: Growth and Body Compositionmentioning
confidence: 99%
“…Intensive selection pressures placed on broiler performance traits, such as increased body weight and growth rate, have resulted in broilers with an increased appetite and therefore also increased voluntary feed intake per day (Siegel and Wisman 1966;Pym and Nicholls 1979;Havenstein et al 1994aHavenstein et al , 2003bO'Sullivan et al 1992b;Schmidt et al 2009;Howie 2010Howie , 2011) (see also section 5). As well as genetic selection, exogenous factors which influence many physiological and behavioural processes can be carefully controlled to increase feed intake and pre-ingestion efficiency.…”
Section: Feed Intake Digestion and Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, today's commercial birds differ very much from those before 1983, in terms of growth, feed conversion efficiency, nutrient utilization, carcass quality and bone characteristics (Havenstein et al, 1994 and2003a). And also, modern diets are much better formulated to meet the nutrient requirements of the fast-growing commercial birds (Havenstein et al, 1994 and2003b). Obviously, the NPP requirements of modern broilers might be lower than those of broiler strains before 1983.…”
mentioning
confidence: 99%